Development of Ar Interactive Learning Media on Ecosystem Material to Improve Critical Thinking Abilities in Grade V Students - Azizah Nur Avivah; Suttrisno; Nurul Mahruzah Yulia (Global Action and Education for Society, 2025)
The lack of use of digital-based learning media causes the social studies learning process to be less than optimal, in addition, in the initial research the critical thinking skills of students in class V of MI Al-Ma'had Roudlotul Huda were low, so the researcher developed augmented reality learning media. The purpose of this study is to develop AR-based digital learning media in IPAS subjects to improve the critical thinking skills of students in class V of MI Al-Ma'had Roudlotul Huda. This research uses the Research and Development research method, with the ADDIE development model: analysis, design, development, implementation, evaluation. This study involved 20 students in class V. The results of the study explained that the augmented reality learning media developed was suitable for use, as evidenced by the validation results of material experts of 93% and media experts of 91%. The results of the product test in the pre-test stage showed a percentage of 63.3% in the